TINGKAT INVESTASI MODAL ASING DALAM PEMBANGUNAN PERTANIAN RATES FOREIGN INVESMENT ON AGRICULTUR DEVELOPMENT - Wahyuningsih, Sri (Universitas Wahid Hasyim, 2005)
This literature research was meant to explore about 1) How many rates of foreign investment in each sector of Indonesian project investmen, 2) how many investment rates on agricultural sector, 3) how investment foreign capital could be divided in each region of Indonesia, 5) what is relation between investment rate and development. The article used description method, secondary data and literature study. From this research was know that rate investment from foreign capital from 2000 year until April 2004 was fluctuated and decreased.For foreign investment, the biggest was manufacturing and industrial sector, next were transportation, trade, and agriculture sector. Agriculture sector got portion of 2,72 percent from total foreign investment. If it was based on regional, the biggest was in Java island, it was 56,47 percent, the remain 43,53 percent of this was located in outer of Java island. Foreign investment constitute necessity requirement, but not sufficiency requirement for development. It must be the others prerequisite in order to effective investment for development. Key Word: Foreign invesment, , agriculture, development.